Evaluation on field performance of vegetable soybean (Glycine max (L.) Merrill) varieties grown at two locations in Malaysia - Nor Hafizah Z.,; Zarina Z.,; Phang, I.C.; Maizatul Akma I.,; Siti Nurul Farhana A.B.,; Mohd Shukor N., (Penerbit Universiti Kebangsaan Malaysia, 2017)
A study was undertaken to investigate the interaction between varieties and soil environments. The experiments were conducted using randomized complete block design (RCBD) with three replications at two different locations representing two different soil types. The locations were; the mineral soil of International Islamic University Malaysia (IIUM) Glasshouse experimental field and the beach ridges interspersed swales (BRIS) soil of Institute Oceanography and Maritime Studies Research Station (IRS) Kuantan, Pahang. The analysis of variance revealed that location contributed significantly to the variations in the number of pod per plant. While, location had no significant effects on the pod yield, number of seeds per plant and plant height. Significant positive correlation was observed between number of pods and seeds per plant for both locations. Between varieties, variety 1 (AGS190) showed the highest marketable pod yield, number of pods and seeds per plant in both locations. The findings from this study could assist the soybean breeders in varietal development, improvement and selection programme in Malaysia.